Reframing Fish Passage Prioritization for Human Nutrition Outcomes - Nicolette Duncan; Ana Horta; John Conallin; Tim Marsden; Abigail J. Lynch; Ivor Stuart (Environmental Management, 2025)
Water control infrastructure forms barriers that fragment river habitats, reducing aquatic biodiversity and the ecosystem services it provides. Irrigation infrastructure, for example, although implemented to support food production, highlights problematic trade-offs against wild food systems like inland fisheries which are a critical food resource for tens of millions of people, particularly in tropical countries. To reduce fragmentation at a broad range of barriers, fish passage technology is sometimes implemented to support migrating fish, aided by frameworks designed to prioritize barriers for remediation. This study critically evaluated 93 fish passage barrier prioritization frameworks globally to explore how they could strategically guide fish passage investments in tropical contexts and identify criteria relevant to delivering on nutrition security outcomes. Results showed prioritization frameworks were ill-equipped to support the broader human development goals that may drive fish passage investments in tropical countries, such as supporting human nutrition under United Nations Sustainable Development Goal (SDG) 2: Zero Hunger. Tropical contexts were underrepresented despite substantial recent fish passage investment, whereas temperate and conservation focused frameworks, particularly from North America, dominated. These findings prompt reflection on the inherent biases in fish passage barrier prioritization frameworks and criteria. Improving understanding of and collaboration with local partners to integrate SDG 2 into future prioritization frameworks could improve fish passage infrastructure and help support better nutrition and food production for communities.

Anguillids: widely studied yet poorly understood—a literature review of the current state of Anguilla eel research - Rose E. Stuart; Jason D. Stockwell; J. Ellen Marsden (Reviews in Fish Biology and Fisheries, 2024)

Rock fishways: Natural designs for an engineered world - Ivor G. Stuart; Timothy J. Marsden; Matthew J. Jones; Matt T. Moore; Lee J. Baumgartner (Ecological Engineering, 2024)

Comparisons of songbirds on sale across online and physical markets in Indonesia - Emily I. Grimwood; Jochen K. Menner; Stuart J. Marsden (Biodiversity and Conservation, 2024)
Unsustainable wildlife trade is a leading threat to biodiversity, not least in Southeast Asia where serious overexploitation of songbirds has precipitated the ‘Asian Songbird Crisis’. While the nature of bird trade in physical markets is fairly well studied, the growing online trade in birds is far less understood, in terms of diversity and traits of birds on offer. Here, online trade, monitored across twelve broad spectrum Indonesian bird-selling Facebook groups over a period of six months in 2022, is compared to published data from physical markets, and from a machine learning web-scrape. Nearly 2,000 individuals of 190 Indonesian species were recorded from Facebook, with 9.5% of species being categorised as Threatened (IUCN 2022), 15.8% protected under Indonesian law, and 17.4% regarded as priority taxa according to the Asian Songbird Trade Specialist Group. These represent similar proportions of species to those from physical market surveys, although physical markets had more individuals of protected species than did Facebook groups. Bird family composition did not correlate between online and physical platforms, with the former dominated by Muscicapidae and the latter by Estrildidae. Controlling for trade volume, online groups had higher species richness than physical markets, although the difference was not significant. Bird ‘communities’ on offer in the individual Facebook groups were both similar to each other, and distinct from those in physical markets, although there was a geographical signature especially in the latter. Results highlight the importance of monitoring online trade as, while there are substantial differences in types of birds sold, it contains a similarly high number of species of conservation concern to physical markets.

Avian diversity and function across the world's most populous cities - James Richardson; Alexander C. Lees; Eliot T. Miller; Stuart J. Marsden (Ecology Letters, 2023)
Understanding the composition of urban wildlife communities is crucial to promote biodiversity, ecosystem function and links between nature and people. Using crowdsourced data from over five million eBird checklists, we examined the influence of urban characteristics on avian richness and function at 8443 sites within and across 137 global cities. Under half of the species from regional pools were recorded in cities, and we found a significant phylogenetic signal for urban tolerance. Site‐level avian richness was positively influenced by the extent of open forest, cultivation and wetlands and avian functional diversity by wetlands. Functional diversity co‐declined with richness, but groups including granivores and aquatic birds occurred even at species‐poor sites. Cities in arid areas held a higher percentage of regional species richness. Our results indicate commonalities in the influence of habitat on richness and function, as well as lower niche availability, and phylogenetic diversity across the world's cities.

Landscape -scale predictors of persistence of an urban stock dove Columba oenas population - James Richardson; Alexander C. Lees; Stuart Marsden (Urban Ecosystems, 2023)
While a few species may thrive in urban areas, urban expansion is a major driver of biodiversity loss. Columbids such as feral Rock Doves ( Columba livia domestica ) and Common Woodpigeon ( Columba palumbus ) have adapted extremely well to the urban environment in Europe and beyond, but the Stock Dove ( Columba oenas ), a bird of farmland and woodland edge in the UK and of national conservation concern, is encountered infrequently in urban areas. Here we explore the multi-scale landscape associations of the little-studied Stock Dove within the urban matrix of Greater Manchester, UK, in order to identify its habitat requirements. We built a pilot model from historical citizen science records to identify potentially occupied sites within the city, and then surveyed these sites for Stock Dove during Spring 2019. We combined the survey results with citizen science records from the same period and described the habitat and landscape characteristics of sites occupied by Stock Dove using four variables at different scales plus twelve unscaled variables. We used a three-stage random forest approach to identify a subset of these variables for interpretation and a subset for prediction for the presence of Stock Dove within these sites. Key variables for predicting Stock Dove presence were their relative abundance in the landscape immediately beyond the core urban area, the greenness (NDVI) of the environment around sites, and the canopy cover of individual trees over 20 m high within sites. Stock Doves tended to be associated with habitats with more surface water during the non-breeding season than the breeding season. Our results highlight the importance of large trees within urban greenspace for this cavity-nesting species, softer boundaries around urban sites for Stock Doves and stock dove presence in nearby areas. While Stock Dove share many traits with species that are successful in the urban environment, they remain relatively poor urban adapters.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Street-level green spaces support a key urban population of the threatened Hispaniolan parakeet Psittacara chloropterus - Matthew Geary; Celia J. Brailsford; Laura I. Hough; Fraser Baker; Simon Guerrero; Yolanda M. Leon; Nigel J. Collar; Stuart J. Marsden (Urban Ecosystems, 2021)
While urbanisation remains a major threat to biodiversity, urban areas can sometimes play an important role in protecting threatened species, especially exploited taxa such as parrots. The Hispaniolan Parakeet Psittacara chloropterus has been extirpated across much of Hispaniola, including from most protected areas, yet Santo Domingo (capital city of the Dominican Republic) has recently been found to support the island’s densest remaining population. In 2019, we used repeated transects and point-counts across 60 1 km 2 squares of Santo Domingo to examine the distribution of parakeets, identify factors that might drive local presence and abundance, and investigate breeding ecology. Occupancy models indicate that parakeet presence was positively related to tree species richness across the city. N-Mixture models show parakeet encounter rates were correlated positively with species richness of trees and number of discrete ‘green’ patches (> 100 m 2 ) within the survey squares. Hispaniolan Woodpecker Melanerpes striatus , the main tree-cavity-producing species on Hispaniola, occurs throughout the city, but few parakeet nests are known to involve the secondary use of its or other cavities in trees/palms. Most parakeet breeding (perhaps 50–100 pairs) appears to occur at two colonies in old buildings, and possibly only a small proportion of the city’s 1500+ parakeets that occupy a single roost in street trees breed in any year. Our models emphasise the importance of parks and gardens in providing feeding resources for this IUCN Vulnerable species. Hispaniola’s urban centres may be strongholds for populations of parakeets and may even represent sources for birds to recolonise formerly occupied areas on the island.

The value of local community knowledge in species distribution modelling for a threatened Neotropical parrot - Rebecca Biddle; Ivette Solis-Ponce; Martin Jones; Stuart Marsden; Mark Pilgrim; Christian Devenish (Biodiversity and Conservation, 2021)
Species distribution models are widely used in conservation planning, but obtaining the necessary occurrence data can be challenging, particularly for rare species. In these cases, citizen science may provide insight into species distributions. To understand the distribution of the newly described and Critically Endangered Amazona lilacina, we collated species observations and reliable eBird records from 2010–2020. We combined these with environmental predictors and either randomly generated background points or absence points generated from eBird checklists, to build distribution models using MaxEnt. We also conducted interviews with people local to the species’ range to gather community-sourced occurrence data. We grouped these data according to perceived expertise of the observer, based on the ability to identify A. lilacina and its distinguishing features, knowledge of its ecology, overall awareness of parrot biodiversity, and the observation type. We evaluated all models using AUC and Tjur R 2 . Field data models built using background points performed better than those using eBird absence points (AUC = 0.80 ± 0.02, Tjur R 2 = 0.46 ± 0.01 compared to AUC = 0.78 ± 0.03, Tjur R 2 = 0.43 ± 0.21). The best performing community data model used presence records from people who were able recognise a photograph of A. lilacina and correctly describe its distinguishing physical or behavioural characteristics (AUC = 0.84 ± 0.05, Tjur R 2 = 0.51± 0.01). There was up to 92% overlap between the field data and community data models, which when combined, predicted 17,772 km 2 of suitable habitat. Use of community knowledge offers a cost-efficient method to obtain data for species distribution modelling; we offer recommendations on how to assess its performance and present a final map of potential distribution for A. lilacina.

Philippine protected areas are not meeting the biodiversity coverage and management effectiveness requirements of Aichi Target 11 - Neil Aldrin D. Mallari; Nigel J. Collar; Philip J. K. McGowan; Stuart J. Marsden (Ambio, 2016)

Impacts of cattle grazing on forest structure and raptor distribution within a neotropical protected area - Renzo P. Piana; Stuart J. Marsden (Biodiversity and Conservation, 2014)

Is There a Role for Human-Dominated Landscapes in the Long-Term Conservation Management of the Critically Endangered Kipunji (Rungwecebus kipunji)? - Claire E. Bracebridge; Tim R. B. Davenport; Vicky F. Mbofu; Stuart J. Marsden (International Journal of Primatology, 2013)

Science-Driven Management of Protected Areas: A Philippine Case Study - Neil Aldrin D. Mallari; Nigel J. Collar; Philip J. K. McGowan; Stuart J. Marsden (Environmental Management, 2013)

The anatomy of population change in a black grouse population 1992–2008 - Matthew Geary; Alan H. Fielding; Stuart J. Marsden (Oecologia, 2012)

Bird community variation across Polylepis woodland fragments and matrix habitats: implications for biodiversity conservation within a high Andean landscape - Huw Lloyd; Stuart J. Marsden (Biodiversity and Conservation, 2008)

Are large‐scale distributional shifts of the blue‐winged macaw ( Primolius maracana ) related to climate change? - Maria Flávia Conti Nunes; Mauro Galetti; Stuart Marsden; Ricardo Scachetti Pereira; A. Townsend Peterson (Journal of Biogeography, 2007)
Aim To evaluate whether observed geographical shifts in the distribution of the blue‐winged macaw ( Primolius maracana ) are related to ongoing processes of global climate change. This species is vulnerable to extinction and has shown striking range retractions in recent decades, withdrawing broadly from southern portions of its historical distribution. Its range reduction has generally been attributed to the effects of habitat loss; however, as this species has also disappeared from large forested areas, consideration of other factors that may act in concert is merited. Location Historical distribution of the blue‐winged macaw in Brazil, eastern Paraguay and northern Argentina. Methods We used a correlative approach to test a hypothesis of causation of observed shifts by reduction of habitable areas mediated by climate change. We developed models of the ecological niche requirements of the blue‐winged macaw, based on point‐occurrence data and climate scenarios for pre‐1950 and post‐1950 periods, and tested model predictivity for anticipating geographical distributions within time periods. Then we projected each model to the other time period and compared distributions predicted under both climate scenarios to assess shifts of habitable areas across decades and to evaluate an explanation for observed range retractions. Results Differences between predicted distributions of the blue‐winged macaw over the twentieth century were, in general, minor and no change in suitability of landscapes was predicted across large areas of the species’ original range in different time periods. No tendency towards range retraction in the south was predicted, rather conditions in the southern part of the species’ range tended to show improvement for the species. Main conclusions Our test permitted elimination of climate change as a likely explanation for the observed shifts in the distribution of the blue‐winged macaw, and points rather to other causal explanations (e.g. changing regional land use, emerging diseases).

A Comparison of Predictive Methods in Extinction Risk Studies: Contrasts and Decision Trees - Matthew S. Sullivan; Martin J. Jones; David C. Lee; Stuart J. Marsden; Alan H. Fielding; Emily V. Young (Biodiversity and Conservation, 2006)

Accumulation of Knowledge and Changes in Red List Classifications within the Family Galliformes1980–2004 - David C. Lee; Stuart J. Marsden (Biodiversity and Conservation, 2006)

Extinction Risk: Predicting, Assessing, Prioritisingand Redressing - Matthew S. Sullivan; Stuart J. Marsden (Biodiversity and Conservation, 2006)

How Well Will Brazil's System of Atlantic Forest Reserves Maintain Viable Bird Populations? - Stuart J. Marsden; Mark Whiffin; Mauro Galetti; Alan H. Fielding (Biodiversity and Conservation, 2005)

Effects of habitat change and geographical variation on the bird communities of two Indonesian islands - Martin J. Jones; Stuart J. Marsden; Mark D. Linsley (Biodiversity and Conservation, 2003)

Bird diversity and abundance in forest fragments and Eucalyptus plantations around an Atlantic forest reserve, Brazil - Stuart J. Marsden; Mark Whiffin; Mauro Galetti (Biodiversity and Conservation, 2001)

Impact of Disturbance on Waterfowl Wintering in a UK Dockland Redevelopment Area - STUART J. MARSDEN (Environmental Management, 2000)

Habitat associations of parrots on the Wallacean islands of Buru, Seram and Sumba - Stuart Marsden; Alan Fielding (Journal of Biogeography, 1999)
Summary Aim To investigate patterns of habitat use in nineteen populations of parrots on three Wallacean islands, and examine the degree to which habitats used by a species can be predicted across islands. Location The Wallacean islands on Buru, Seram and Sumba. Methods A logistic regression method was used to relate the presence/absence of parrot species at census plots to vegetation axes derived from ‘gross’ habitat parameters such as altitude, tree sizes, and percentages of vegetation coverage at different strata. Receiver Operating Characteristic Plots were then used to test predictions of habitat use by conspecific populations on the nearby and distant islands, and by different parrot species on the same island. Results Parrots on Buru and nearby Seram tended to be associated with open‐canopied lowland forests, while on the distant and low‐lying island of Sumba, the preference was for closed‐canopy forests at higher altitudes. There were usually close affinities in habitat usage by conspecific populations on the two nearby islands. One exception was where the species occurred on the two islands as separate subspecies. Habitat preferences on Sumba, however, were so distinct that paradigms developed for Buru and Seram failed to predict distributions on this distant island. Main conclusions For populations on more distant islands, it will usually be better to predict habitat use by considering the habitat used by other parrot species occurring on that island, than a conspecific population from another region. Conservation research programmes which concentrate parrot study on just one or two islands in every region of Wallacea may be more successful than those which ‘run through’ several islands in a group, but which miss out whole regions.

Changes in Bird Abundance following Selective Logging on Seram, Indonesia - Stuart J. Marsden (Conservation Biology, 1998)

Changes in Bird Abundance following Selective Logging on Seram, Indonesia - Stuart J. Marsden (Conservation Biology, 1998)
Timber concessions cover 90% of forest on some Indonesian islands, but the effects of logging on endemic‐rich island avifaunas are poorly known. I used a point count method to estimate population densities of Seram’s lowland birds in recently logged forest and in unlogged forest. Few bird species were excluded from logged forest, and several species were similarly common in the two habitats. Bird species diversity (the Shannon index) was, however, significantly lower in logged forest. The proportion of Seram’s species that declined after logging was comparable to that reported from species‐rich continental areas. There were also some similarities in the types of birds most affected. Species that were rare in unlogged forests were no more likely to decline after logging than were common ones. Although birds with small global ranges fared no worse than widespread species, several endemic forms were seriously affected. So many of the region’s taxa are endemic to single islands that logging concessions need to be examined at an individual island level and the presence or absence of endemic forms of susceptible genera considered. Cambios en la Abundancia de Aves Después de Tala Selectiva en Seram, Indonesia Cerca del 90% de los bosques en ciertas islas Indonesias están concesionados a compañías madereras, pero se conoce poco de los efectos de la tala sobre la avifauna rica en endemismos asociada a estas islas. Utilicé un método de conteo por puntos para estimar las densidades poblacionales de las aves de tierras bajas en Seram, en bosque talado recientemente y en bosque no talado. Pocas especies de aves fueron excluidas del bosque talado, y varias especies fueron similarmente comunes en los hábitats. Sin embargo, la diversidad de aves (mediante Índice de Shannon) fue significativamente menor en el bosque talado. La proporción de especies de Seram que declinaron después del talado fue comparable a la reportada para áreas continentales de alta riqueza de especies. También hubo similitud en el tipo de aves más afectadas. Las especies raras y comunes en bosques no talados tenían la misma posibilidad de declinar después del talado. Aunque las especies con pequeños rangos de distribución global no corrieron peor suerte que las especies de amplia distribución, hubo varias formas endémicas que fueron afectadas seriamente. Debido a que muchas taxa de la región son endémicas a una sola isla, las concesiones madereras deben ser examinadas a nivel individual, y se debe considerar la presencia o ausencia de formas endémicas.